P557 Long-term outcomes following laparoscopic ileocecal resection without any residual lesion for Crohn's disease: a single-center observational study. (27th May 2021) - Ge, X; Zhou, W
Abstract: Background: To describe the characteristic of Crohn's disease (CD) patients undergoing ileocecal resection, and to analyze the long-term outcomes following surgery. Methods: A retrospective study on patients undergoing ileocecal resection without any from residual disease in the remnant intestine from July 2011 to March 2020 was conducted. The clinical data and the following outcomes were evaluated. Results: Among 86 CD patients, the mean disease duration was 33.4 months, 40 patients had perianal fistula. 53 patients underwent surgery due to stricture, 26 was perforation, and 7 was failure of medical therapy. 27 (31.4%) patients suffered postoperative complications. Mean follow-up was 44.4 months, 47 (54.7%) patients had an endoscopic recurrence with 9 were non-anastomotic recurrence, 20 were anastomotic recurrence, and 18 were both anastomotic and non-anastomotic recurrence, and 4 patients had a surgical recurrence. Furthermore, 41 (47.7%) had postoperative prophylaxis with 22 (25.6%) azathioprine and 17 (19.8%) infliximab. 45 (52.3%) patients were without postoperative prophylaxis, 19 (42.2%) had an endoscopic recurrence, and 26 (57.8%) had none endoscopic recurrence. The penetrating disease and lower skeletal muscle index were independent risk factors for endoscopic recurrence. Conclusion: CD patients with penetrating disease or lower skeletal muscle index were suggested to have earlier postoperative prophylaxis after ileocecal resection without any from residual disease in the remnant intestine.